Expression of TREM‐1 in hepatic stellate cells and prognostic value in hepatitis B‐related hepatocellular carcinoma - Rui Liao; Tai‐Wei Sun; Yong Yi; Han Wu; Yiwei Li; Jiaxing Wang; Jian Zhou; Ying‐Hong Shi; Yunfeng Cheng; Shuang‐Jian Qiu; Jia Fan (2012)
Hepatocellular carcinoma (HCC) is a typical inflammation-related malignancy characterized by high postoperative recurrence and metastasis. Although several inflammatory cells and inflammatory signatures have been linked to poor prognosis, the inflammation-associated molecular mechanisms of HCC development and progression are largely unknown. Here we show that triggering receptor expressed in myeloid cells (TREM)-1, a transmembrane receptor expressing in myeloid cells, was also expressed in tumor-activated hepatic stellate cells (HSCs) and associated with the aggressive behavior of HCC cells. Enzyme-linked immunosorbent assay was used to measure the expression levels of soluble TREM-1 (sTREM-1) in activated hepatic stellate cells supernatant and 92 preoperative and postoperative plasmas of patients with malignancy and/or benign liver tumor/disease, respectively. Expression levels of TREM-1 were assessed by immunohistochemistry in tissue microarray from 240 patients with HCC. As a result, increased secretion of sTREM-1 from activated HSCs was observed after co-culture with HCC cell lines (P < 0.001), and conditioned medium collected from activated HSCs/cancer associated myofibroblasts (CAMFs) with or without agonist/inhibitor of TREM-1 significantly changed the migratory ability of HCC cells. The levels of sTREM-1 were significantly higher in patients with HCC than those with benign liver tumors (P < 0.005). Peritumoral density of TREM-1 was shown to be an independent prognosis predictor according to univariate (P < 0.001 for both overall survival and time to recurrence) and multivariate analysis (P = 0.008 for overall survival; P = 0.005 for time to recurrence). Thus, these observations suggest that TREM-1 is related to the aggressive tumor behavior and has potential value as a prognostic factor for HCC.